BEAMDULAC-BL code for 3D simulation of electron beam dynamics taking into account beam loading and coulomb field - Bondarenko, T.V.; Masunov, E.S.; Polozov, S.M. (Вопросы атомной науки и техники, 2013)
BEAMDULAC-BL 3D code is designed last years to study the beam dynamics in linac taking into account both Coulomb and RF self field. The code versions for traveling and standing wave linacs are ready for operation. The especially designed numerical methods and algorithms used for the code design are discussed. Specific computing problems, abilities of the code and future design plans are presented. Розглянуто алгоритми та чисельні методи, використані у новій версії програми BEAMDULAC-BL для тривимірного чисельного моделювання динаміки з урахуванням як квазістатичного поля, так і навантаження струмом. Обговорюються специфічні проблеми, що виникли при розробці, основні можливості програми та плани її подальшого розвитку. Рассмотрены алгоритмы и численные методы, использованные в новой версии программы BEAMDULAC-BL для трехмерного численного моделирования динамики с учетом как квазистатического поля, так и нагрузки током. Обсуждаются специфические проблемы, возникшие при разработке, основные возможности программы и планы ее дальнейшего развития.